Small lymphocytic lymphoma in true trilineage hematopoietic tissue within heterotopic ossification in an enucleated blind painful eye: a case report - Alfredo Borgia; Sofia Manara; Monica Balzarotti; Paolo Vinciguerra; Alessandra Di Maria (Journal of Medical Case Reports, 2020)
Abstract Background The finding of hematological malignancies within bone marrow in heterotopic ossification has been reported only a handful of times previously in the literature. We described a case of true trilineage hematopoiesis in an excised area of heterotopic ossification from an enucleated blind painful eye. Case presentation A 70-year-old Caucasian man, positive for asymptomatic lymphoplasmacytic lymphoma, presented with a blind painful right eye in our ophthalmology department to evaluate enucleation bulbi. After enucleation, a histopathologic examination revealed the presence of intertrabecular infiltration in the metaplastic bone marrow of non-Hodgkin B lymphoma, with small lymphocytes, with similar characteristics to the already known disease. Conclusion This uncommon case reveals the possibility of the localization of malignant cells within bone metaplasia of intraocular ossification in an enucleated blind painful eye. From a practical point of view, a careful systematic histopathological examination of all resected tissues in patients with a history of malignant neoplastic pathology is necessary to confirm the diagnosis and exclude occult malignancies.